Петро Сокальський як діяч Імператорського Товариства сільського господарства Південної Росії (1869-1871) - Сорокіна, К. (Чорноморська минувшина, 2020)
Презентоване дослідження являє собою спробу комплексного аналізу долі участі українського композитора та публіциста Сокальського Петра Петровича (1832-1887) в лавах Імператорського товариства сільського господарства Південної Росії протягом 1869- 1871 рр. Зокрема, з’ясовано, що протягом означеного періоду Петро Петрович обіймав у Товаристві одразу дві посади – секретаря товариства та редактора його друкованого органу – «Записок Императорского Общества сельского хозяйства южной России». В зв’язку з цим, у статті не лише надано огляд роботи Петра Сокальського на базі численних галузевих комісій товариства, але й здійснено бібліографування публіцистичної спадщини автора в зазначеному часописі Товариства. Складений перелік публікацій Петра Петровича на сільськогосподарську тематику винесено у якості додатку до статті. The presented study is an attempt to comprehensively analyze the share of the participation of Ukrainian composer and publicist Sokalskyi Petro Petrovych (1832-1887) in the Imperial Society of Agriculture of Southern Russia during 1869-1871. Based on the materials of volumes of «Notes of the Imperial Society of Agriculture of Southern Russia» and historical reviews of the activities of the society, it was found out that during this period Petro Petrovych held in society two positions at once – the secretary of the society and the editor of its printed edition – the above-mentioned «Notes of the Imperial Society of Agriculture of Southern Russia». In this regard, the author of the article not only provides an overview of the work of Petro Sokalskyi in the numerous branch commissions of the society, among which – the commission for the development of sheep farming in the south of the empire; the commission for the development of wood farming; the chemical commission at the winemaking exhibition; etc.; but also tries to compile the bibliography of Petro Sokalskyi articles in the printed edition of the society. The compiled list of Petro Petrovych's publications on agricultural topics is presented as an addition to the article. These articles were the review of the problems of agriculture in the south of the empire in different years; the discussion of measures of encouraging the sheep farming and the wood farming in the region; the description of the results of the exhibition of viticulture and winemaking; and so on. It is also interesting to note that except Petro Petrovych, among the members of the society there were also his older brothers – scientist and publicist Ivan Sokalskyi and publicist Mykola Sokalskyi. This fact and the multifaceted activity of Petro Petrovych in the Imperial Society of Agriculture of Southern Russia opens the horizons for further careful study of the topic and for broader historiographical analysis, because there are a number of unresolved thematical issues.